Maps of meaning: journeys of first year engineering students. (2nd November 2022) - Kopparla, Mahati; Nguyen, Trang T.; Woltering, Steven
ABSTRACT: Undergraduate STEM retention has been a longstanding concern. Specifically, majors such as engineering have experienced a high dropout rate consistently in the past several decades. This study is aimed at understanding factors contributing to making the engineering major challenging, and individual factors that help first-year engineering students persevere in the major. Eight first-year engineering students participated in the study by completing an illustrated road map sketch of their first-year experiences and a semi-structured interview. All participants considered the engineering major challenging due to the amount of time and effort required to be successful in the courses. Being academically underprepared for first-year courses was a drawback, but only some participants were discouraged by the academic challenges. Most importantly, students' perception of academic and social fit within the major influenced their self-efficacy, help-seeking behaviour, and intent to persist.